Micro-world of "The airplane of the muda": A systemic approach to Lean (2015)
ABSTRACT: “The airplane of the muda” is a game on a production line, used for practical training on Lean Manufacturing (LM). The aim of this paper is to provide a computer model for the game that approaches it from a systems perspective, to broaden its scope beyond the traditional tactical and operational end, to understanding and strategic decision making. The integration of all this with a challenging case (i.e. maximising cash flow) on an interface in which users can make line balancing decisions, 5S and 5 whys, makes for a computer micro-world on system dynamics. Users can test their hypotheses, receive feedback, and analyse behaviour, not only in the short term, but over a period of 25 years, while enabling instruction on simple LM tools, as well as underlying concepts and complex behaviours of business improvement. Moreover, the results obtained have pointed out interactions between the production, finance, customer, and improvement subsystems, which may lead to improved understanding of business transformation processes.